Reestablish immune tolerance in rheumatoid arthritis - Shuai, Ziqiang; Zheng, Shuang; Wang, Kang; Wang, Jian; Leung, Patrick S. C.; Xu, Bin (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is a chronic progressive autoimmune disease. Despite the wide use of conventional synthetic, targeted and biologic disease modifying anti-rheumatic drugs (DMARDs) to control its radiological progress, nearly all DMARDs are immunologically non-selective and do not address the underlying immunological mechanisms of RA. Patients with RA often need to take various DMARDs long-term or even lifelong and thus, face increased risks of infection, tumor and other adverse reactions. It is logical to modulate the immune disorders and restore immune balance in patients with RA by restoring immune tolerance. Indeed, approaches based on stem cell transplantation, tolerogenic dendritic cells (tolDCs), and antigen-based tolerogenic vaccination are under active investigation, and some have already transformed from wet bench research to clinical investigation during the last decade. Among them, clinical trials on stem cell therapy, especially mesenchymal stem cells (MSCs) transplantation are most investigated and followed by tolDCs in RA patients. On the other hand, despite active laboratory investigations on the use of RA-specific peptide- / protein-based tolerogenic vaccines for T cell, clinical studies on RA patients are much limited. Overall, the preliminary results of these clinical studies are promising and encouraging, demonstrating their safety and effectiveness in the rebalancing of T cell subsets; particular, the recovery of RA-specific Treg with increasing anti-inflammatory cytokines and reduced proinflammatory cytokines. Future studies should focus on the optimization of transplanted stem cells, the preparation of tolDCs, and tolerogenic vaccines with RA-specific protein or peptide, including their dosage, course, and route of administration with well-coordinated multi-center randomized clinical control researches. With the progress of experimental and clinical studies, generating and restoring RA-specific immune tolerance may bring revolutionary changes to the clinical management of RA in the near future.